KANDUNGAN LOGAM BERAT TIMBAL (Pb ) PADA SEDIMEN DAN SIPUT Strombus Canarium DI PERAIRAN PANTAI PULAU BINTAN - Monika Siska; Syafruddin Nasution (Program Pascasarjana Universitas Riau, 2011)
The investigation was conducted early 2008 at North Bintan island waters, Riau IslandsProvince. The sample of sediment and snail S. canarium has been taken from four locationsthose were Busung, Lobam, Sebung, and Tanjung Bakau coastal waters. Metal contentanalysis conducted by use Atomic Absorption Spectrophotometer (AAS) type Solar 969 AA,both in sediment and snail. The average content of heavy metal Pb in sediment over satationwas 2,99 ppm. While the average metal concentration in the sanil was 3.80 ppm. The highestcontent of heavy metal in sediment and snail was obtained at Lobam coastal waters, whichwas an area that close to the town, industries, and shipping activities. The was a strongpositif relationship between concentration of heavy metal Pb in sediment and in the sail (sig< 0.05).